Self Image Making of the Diasporic Artists: "The Sousveillance Strategies in the Diasporic Art of Middle Eastern Diaspora" - Balca Arda (Mashriq & Mahjar, 2017)
I explore in this paper how Middle Eastern diaspora’s art that I call “selfie art” resists against surveillance techniques and technologies in everyday life beyond territorial borders such as public stigma and stereotyping in the host countries in North America. My analysis is composed of three stages: (1) The study of self-surveillance as a method of sousveillance and how self-exposure becomes an object of art; (2) the relation between self-design and politico-ethical allegiance in the visual abundant society through the case of the imagery of Middle Eastern diaspora; (3) ethnographic observations in diasporic art events as well as in-depth interviews with artists and content analysis of various online and offline artworks. I argue that the sousveillance strategies of diasporic art coincide with the resisting communities that negotiate with technologies of surveillance to lead a state of equiveillance in the visual public sphere.